2009
DOI: 10.3945/ajcn.2009.27543
|View full text |Cite
|
Sign up to set email alerts
|

Blunting of insulin inhibition of proteolysis in legs of older subjects may contribute to age-related sarcopenia

Abstract: At moderate availability, the effect of insulin on LPB is diminished in older human beings, and this effect may be mediated through blunted Akt-PKB activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(155 citation statements)
references
References 34 publications
4
143
1
Order By: Relevance
“…These findings are consistent with other studies that have reported a reduction in response to insulin [30,32,37,39,42,44] with the exception of three studies, which did not observe any significant change in MPB [45,47,48]. This might well be due to anabolic resistance to insulin in a relatively older study population and the presence of diabetes mellitus.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with other studies that have reported a reduction in response to insulin [30,32,37,39,42,44] with the exception of three studies, which did not observe any significant change in MPB [45,47,48]. This might well be due to anabolic resistance to insulin in a relatively older study population and the presence of diabetes mellitus.…”
Section: Discussionsupporting
confidence: 82%
“…In the early post-prandial period, plasma amino acid levels and [1-13 C]phenylalanine enrichments tended to be higher in the young versus the older group. This apparent delay in plasma amino acid concentrations and enrichments can be accounted for by either a delayed digestion and/or absorption rate (Boirie et al 1997;Volpi et al 1999;Koopman et al 2009b;Pennings et al 2011b), and/or a greater amino acid uptake secondary to the compensatory hyperinsulinemia (Hatzakorzian et al 2011) (Fig.1b), and/or an attenuated inhibition of the post-prandial reduction in protein breakdown (Wilkes et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Several groups have identified anabolic resistance in human muscle (21)(22)(23)(24)(25) and Rennie's group have reported a blunting of both the stimulation of protein synthesis by amino acids (23) and the inhibition of proteolysis by insulin (25) in the healthy elderly compared with younger adults. This is linked to anabolic signalling deficits which mean that the nutrient signal provided by essential amino acids is not sensed or transduced as well by old muscle as it is by young muscle, resulting in a lower response of protein synthesis to the same nutrient stimulus.…”
Section: Anabolic Resistance: Dietary Protein Intakesmentioning
confidence: 99%